Anti-α-enolase antibody limits the invasion of myeloid-derived suppressor cells and attenuates their restraining effector T cell response. (3rd May 2016) - Cappello, Paola; Tonoli, Elisabetta; Curto, Roberta; Giordano, Daniele; Giovarelli, Mirella; Novelli, Francesco
ABSTRACT: Pancreatic Ductal Adenocarcinoma (PDA) is a very aggressive tumor for which effective therapeutical strategies are still lacking. Globally, the 5 y survival rate is 5–7% and surgery is the only potentially curative treatment. Immunotherapy represents a novel possibility for treating PDA, and myeloid-derived suppressor cells (MDSC), which are increased in cancer patients and correlate with metastatic burden and cancer stage, offer a new target in cancer therapy. We have previously shown that antibodies against the PDA-associated antigen α-enolase (ENO1) are detected in more than 60% of PDA patients and correlate with a better prognosis. Furthermore, ENO1-DNA vaccination in mice induced anti-ENO1 antibodies that mediated antitumor activity. In this study, the effects of anti-ENO1 binding on MDSC functions and on the T cell response were evaluated. Here, we show that MDSC express ENO1 on their surface, which increased after LPS stimulation. Moreover, anti-ENO1 mAb inhibited adhesion to endothelial cells, as well as in vitro and in vivo migration. Similarly, after ENO1 mAb treatment of MDSC, arginase activity decreased, while the secretion of pro-inflammatory cytokines (particularly IL-6) increased, and co-stimulatory molecule expression and suppression functions were only partially affected. Finally, we found that activated T cells in the presence of anti-ENO1 mAb-treated MDSC increased IFNγ and IL-17 secretion and decreased IL-10 and TGFβ secretion compared to control MDSC. In conclusion, anti-ENO1 antibodies may inhibit in vivo the infiltration into the tumor microenvironment of MDSC, and attenuate their restraining of effector T cell response, opening a new perspective to render PDA immunotherapy more effective.